Phase transitions induced by exchange coupling, magnetic field, and temperature in a strongly correlated molecular trimer with a triangular topology. Issue 37 (15th September 2022) - Nan, Nan; Zhou, Wang-Huai; Zhang, Jun; Li, Wei; Yang, Jun-Tao; Chen, Jie; Xiong, Yong-Chen; Tan, Guo-Long
Abstract : Phase transitions and Kondo behaviors in a molecular trimer device with a triangular topology manipulated by inter-monomer exchange coupling with and without magnetic fields and at zero and nonzero temperatures. Abstract : Regulating the physical properties such as the quantum phase and the Kondo effect of molecular electronic devices near critical points may play a key role in increasing the robustness of quantum memory, which is a crucial component in quantum information processing. Molecules with a triangular topology are ideal prototypes to reveal the competition among magnetic frustration, Kondo screening, and local inter-molecule exchange interactions. Herein, motivated by a recent work investigating the single-electron tunneling through a redox-active edge-fused porphyrin trimer by using a Hubbard dimer model [J. O. Thomas, J. K. Sowa, B. Limburg, X. Bian, C. Evangeli, J. L. Swett, S. Tewari, J. Baugh, G. C. Schatz, G. A. D. Briggs, H. L. Anderson and J. A. Mol, Chem. Sci., 2021, 12, 11121], we studied the phase transition, the electronic transport, and the thermodynamical properties of a real molecular trimer structure organized in a triangular topology, with and without an external magnetic field, and at zero and non-zero temperatures. Both the Hubbard electron–electron interaction and the Heisenberg exchange interaction are fully taken into account, with the aid of the state-of-the-art numerical renormalization group method. Various kinds of Kondo behaviors and quantum phase transitions are demonstrated, due to the competition among the Ruderman–Kittel–Kasuya–Yosida interaction, the direct exchange coupling, and the Zeeman effect. Our findings may offer deep insights into the manipulation of the quantum phase and the Kondo behavior in a molecular trimer with a triangular topology.